Meta‐Analysis of Recurrence‐Free Survival or Disease‐Free Survival as a Potential Surrogate Endpoint for Overall Survival in Esophageal Cancer Trials - Uchechukwu Love Anyaduba; Oluwatosin Qawiyy Orababa; Zion Faye; Nazia Rashid; Jason Shafrin; Gregory Reardon (Cancer Reports)
ABSTRACT Background Cancer trials increasingly use surrogate endpoints, but it is unclear how well recurrence‐free survival (RFS) or disease‐free survival (DFS) specifically predict overall survival (OS) in resectable esophageal cancer (EC). Methods A systematic literature review identified trials with RFS/DFS and OS endpoints. A meta‐analysis assessed RFS/DFS as surrogates for OS, estimating pooled hazard ratios (HRs) from trial HRs. Forest plots and heterogeneity tests showed effect sizes and pooled estimates. Unweighted linear regression and weighted sensitivity analysis estimated the correlation between OS and RFS/DFS, producing a regression plot. Results Of 975 articles identified, 11 met the criteria. The pooled HR for OS and RFS/DFS was 0.90 and 0.87, respectively. The primary analysis showed a strong Pearson correlation between RFS/DFS and OS (ρ = 0.89, p < 0.001). Conclusion Subject to known methodological limits, RFS/DFS was demonstrated to be a potentially suitable surrogate endpoint for OS in resectable EC.